Pemanfaatan Digital Marketing Bagi Usaha Mikro, Kecil Dan Menengah Kue Emak Johati Di Desa Sukajaya Kalianda - Khaidarmansyah; Meliyanti; Nizar (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
This community service aims to improve digital-based financial management skills among micro, small and medium enterprises (MSMEs) Vista Abadi, Banjar Negeri Village, Way Lima District, through training in using the Buku Warung application. The methods used in this training include socialization about the importance of good financial management, freezing the use of applications, and direct practice by participants. The results of the training showed a significant increase in digital literacy and participants' ability to operate the Buku Warung application. Approximately 70% of participants switched from manual recording methods to digital recording, which increases accuracy and efficiency in financial management. Positive feedback from participants represents satisfaction with the material presented. Although the direct impact on business operations took longer to evaluate, participants reported improvements in cash flow management. It is hoped that this training can contribute to the growth of MSMEs and improve community welfare in the digital era.